2011
DOI: 10.1126/science.1208747
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Emergence of Bacterial Antibiotic Resistance in Connected Microenvironments

Abstract: The emergence of bacterial antibiotic resistance is a growing problem, yet the variables that influence the rate of emergence of resistance are not well understood. In a microfluidic device designed to mimic naturally occurring bacterial niches, resistance of Escherichia coli to the antibiotic ciprofloxacin developed within 10 hours. Resistance emerged with as few as 100 bacteria in the initial inoculation. Whole-genome sequencing of the resistant organisms revealed that four functional single-nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
475
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 495 publications
(499 citation statements)
references
References 23 publications
11
475
3
Order By: Relevance
“…It has been shown that even when bacteria was exposed to 200 times its minimum inhibitory concentration (MIC), it can develop resistance within 10 hours [57]. This suggests that our previous understanding that bacterial resistance is directly related to being exposed to below-MIC concentrations of antibiotics [58] may be incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that even when bacteria was exposed to 200 times its minimum inhibitory concentration (MIC), it can develop resistance within 10 hours [57]. This suggests that our previous understanding that bacterial resistance is directly related to being exposed to below-MIC concentrations of antibiotics [58] may be incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose gradient or chemotherapy gradients have been used to study the phenotypic progression of cancer in complex environments (4,5); now we add the compartmentalization of small, possibly clonal, communities within the gradient. Just as rapid fixation of drug-resistant bacterial mutants in a metapopulation can occur in an environment with drug gradients and connected microhabitats (6)(7)(8), we demonstrate that an ecologically designed microenvironment, with drug gradients and connected microhabitats, can drive the rapid emergence of resistance in MM. We then use transcriptome sequencing of the far more complex (than in bacteria) genomic substitution patterns in the evolved MM cancer cells to address the question: What is the role of both substitutions and nonsubstitutions in the evolved genomes of the resistant cells in driving drug resistance?…”
mentioning
confidence: 99%
“…Examples include viral adaptation during infection (1), the emergence of antibiotic resistance (2), artificial selection in biotechnology (3), and cancer (4). Rapid adaptation is characterized by three key features: (i) the availability of strongly advantageous traits accessible by rare mutations, (ii) an elevated mutation rate (1), and (iii) a dynamic population size (5).…”
mentioning
confidence: 99%